Canva Animated Video Media to Improve History Learning Activities of Class X Students of Bastren Nurussalam Vocational School - M. Izza Fajar Sa'bana; Rina Rohmawati; M. Iqbal Ibrahim Hamdani (Historia, 2026)
This study aims to improve the learning activity of Grade X PBS students at SMK Bastren Nurussalam in history lessons through the use of Canva-based animated video media. Initial observations indicated that students showed low learning engagement, such as lack of attention, minimal participation in discussions, and weak analytical skills. Using Classroom Action Research (CAR) conducted over two cycles, animated video media was implemented as an instructional innovation. The results revealed a significant increase in students' learning activity, marked by greater enthusiasm, active participation, and improved understanding of the material. Canva-based videos proved effective in presenting historical content in a more engaging and contextual way, aligning with the digital-native characteristics of today's students. Therefore, the use of Canva-based animated video media is recommended as an effective strategy to enhance the quality of history teaching in schools.